Adsorpsi Ion Logam Pb (II) Menggunakan Karbon Aktif Teraktivasi H3PO4 dari Cangkang Buah Karet - Rahayu, Martina Asti; Qisthi, Zummul; Wijaya, Dhian Eka; Gusti, Diah Riski; Lestari, Intan (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
The use of activated carbon in Indonesia is increasingly expanding in line with the increasing demand for activated carbon, so it is necessary to develop activated carbon preparation using many raw materials and activators. Activated carbon from the shell of  rubber fruit using H3PO4 as activator has been synthesized  for adsorption of Pb (II) metal ion. The objective of this research is to find out the best concentration of H3PO4 activator on the activation of activated carbon of rubber shell, to know its ability as Pb (II) metal ion absorbent in solution and to know the characteristics of activated carbon. Parameters observed included activator concentration, pH and initial concentration of adsorbate. The results showed that the optimum activator concentration on preparation of activated carbon from the rubber shell was H3PO4 20% with the Pb(II)efficiency adsorption of 98,20%, while the optimum pH found at 4 with the adsorption capacity of 87,48% . The adsorption capacity increases with the concentration of adsorbate up to 30,73 mg/g at a concentration of 175 ppm. Activated carbon from rubber shell activated with H3PO4 has moisture content 9,22%, moisture content of 23,53%, ash content of 10,27% and carbon bonded 66,20% fulfilling the requirements of SNI 06-3730-1995 . The results of morphological analysis and carbon constituents using SEM-EDX showed that activated carbon contained 93,91% carbon element and Pb element concentration contained in activated carbon after adsorption of 1,13%.